(untitled) (Research, Society and Development, 2023)
In search of better agricultural production, farmers are looking for new technologies and among these one that is widely used are biostimulants, which are agrochemicals that can promote various benefits in cultivated plants. Biostimulants based on seaweed extracts of the Ascophyllum nodosum species have been widely marketed, as they present relevant responses in the production of different cultures, especially when these are subject to cultivation in environments under stress conditions. These products promote an increase in the absorption of nutrients and water by plants, in addition to influencing hormonal activity. The objective was to evaluate the effects of different doses of the biostimulant based on seaweed extracts of the species Ascophyllum nodosum, applied via foliar application, in corn. The research was carried out between March and July 2022, in Carmo do Rio Claro-MG, conducted in a Randomized Block Design (DBC) with 5 treatments (doses of 0, 50, 100, 150 and 200 mL.ha-1 of the biostimulant ) and 7 repetitions, totaling 35 experimental units. The following parameters were analyzed: stem diameter, plant height, root length, leaf length, leaf width, thousand grain weight, production in 200 m² and production in Kg.ha-1. The application of the biostimulant based on seaweed extracts of the Ascophyllum nodosum species (Acadian commercial product) obtained significant results in the growth and development of corn plants, resulting in significant increases in grain productivity, especially when applied at a dose of 200 mL.ha-1.